2017
DOI: 10.1002/clen.201500670
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Growth, Yield, and Pigmentation of Mung Bean Plants UsingOchrobactrum intermediumCP‐2 as Bioinoculant

Abstract: The selection of strains for production of biofertilizers is of primary importance. A strain with diverse growth promoting activities, especially the nitrogen fixation and phosphate solubilization, has highest preference over those with just one activity. In the present study, a symbiotic nitrogen fixing bacterium was isolated from the root nodules of chickpea and characterized as Ochrobactrum intermedium CP‐2 on the basis of biochemical tests and partial 16S rRNA gene sequencing and blast analysis. Besides fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Maheshwari et al (2019) and humans (Hu et al 2020). The results of the present study were in accordance with those of Lee et al (2020) who reported plant growth-promoting activity of Brucella anthropi strain T16R-87 and Saini et al (2017) who observed the ability of Ochrobactrum intermedium CP-2 chickpea isolate to produce siderophore. Endophytic bacterial isolate CRBE1, identified as Priestia megaterium in the present study, was previously known as Bacillus megaterium (Biedendieck et al 2021), produced HCN along with ACC utilization, while isolate CRBE7 (Microbactrum haematophilum) showed positive reaction for siderophore and HCN production.…”
Section: Discussionsupporting
confidence: 91%
“…Maheshwari et al (2019) and humans (Hu et al 2020). The results of the present study were in accordance with those of Lee et al (2020) who reported plant growth-promoting activity of Brucella anthropi strain T16R-87 and Saini et al (2017) who observed the ability of Ochrobactrum intermedium CP-2 chickpea isolate to produce siderophore. Endophytic bacterial isolate CRBE1, identified as Priestia megaterium in the present study, was previously known as Bacillus megaterium (Biedendieck et al 2021), produced HCN along with ACC utilization, while isolate CRBE7 (Microbactrum haematophilum) showed positive reaction for siderophore and HCN production.…”
Section: Discussionsupporting
confidence: 91%
“…The genera Ochrobactrum belonging to subclass alpha (α) proteobacteria have. been found as an endophyte in various leguminous plants [44]. The occurrence of genera Paenochrobactrum (subclass α‐proteobacteria) as an endophyte has been reported in a single study from the shrub Litsea cubeba [45].…”
Section: Discussionmentioning
confidence: 99%